Distributed event-triggered scheduling in networked interconnected systems with sparse connections - Guan, Yanpeng; Ping, Guonan; Zheng, Wei Xing; Yao, Huijuan (Neurocomputing (Amsterdam), 2020)
This paper is concerned with the problem of distributed event-triggered scheduling for a class of interconnected systems with limited coupling connections. Different from the existing studies, in the considered interconnected system, each remote control station is allowed to retrieve event-triggered sampled-data from interacting control stations, while the number of coupling communication connections is upper bounded in a κ-sparse sense rather than permanently fixed. The distributed event-triggered scheduling problem subject to such a cardinality constraint is nontrivial due to its combinatorial nature. Different from the existing l1 norm based iterative convexification approach, a direct design approach based on mixed-integer programming is proposed to handle the cardinality constraint. Furthermore, an explicit κ-sparse distributed scheduling algorithm is designed for the networked interconnected system via the Lyapunov functional method and some matrix manipulations. The proposed approach is finally applied to a three-machine power system to illustrate its effectiveness.